1981
DOI: 10.3168/jds.s0022-0302(81)82570-2
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Son's Modified Contemporary Comparison from Pedigree Information

Abstract: Son's modified contemporary comparison Predicted Differences and modified contemporary deviations based on daughters' first lactations only and on all lactations were predicted for milk and fat yield and fat percent from pedigree information. Pedigree records included Predicted Differences and modified contemporary deviations for male relatives and modified contemporary deviations and Cow Index on first available records for female relatives. For a son's dam, however, first two and first three available record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

1982
1982
1998
1998

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 12 publications
(21 reference statements)
3
4
0
Order By: Relevance
“…Westell and Van Vleck (17,18) summarized studies using Northeast AI sire comparisons (NEAISC) and intraherd cow evaluations (1,7) in the Northeast (NE ETA). Similar studies have been done with USDA evaluations (2,3,4,5,9,10,12).…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…Westell and Van Vleck (17,18) summarized studies using Northeast AI sire comparisons (NEAISC) and intraherd cow evaluations (1,7) in the Northeast (NE ETA). Similar studies have been done with USDA evaluations (2,3,4,5,9,10,12).…”
Section: Introductionsupporting
confidence: 57%
“…Many reports have suggested that dam information does not predict son or daughter genetic value as well as theoretically possible (2,4,5,6,9,10,12,17,18). Evaluations for dams that include other than first lactation records have produced regressions for offspring on dams that are much smaller than genetic theory predicts.…”
Section: Introductionmentioning
confidence: 99%
“…The use of the maternal grandsire model (7) complicates the theoretical regression but will not be considered here because sire evaluation in pedigree analyses previously have not considered the maternal grandsire model (1,2,4,5,6,8).…”
Section: Discussionmentioning
confidence: 99%
“…However, even if preferential treatment could cause the heterogeneity, the use of within-herd variance or within-herd coefficient of variation has been found to be insensitive in detecting herds with preferential treatment (Graham, Smith and Gibson, 1991). Using only the first records of cows for bull dam selection, the overestimation could be reduced (Rothschild, Douglass and Powell, 1981;Pedersen, 1991). On the other hand, the accuracy of bull dam evaluation would then be reduced.…”
Section: Bias In Pedigree Indicesmentioning
confidence: 99%